Sea ice in the northern North Atlantic through the Holocene: Evidence from ice cores and marine sediment records. (1st December 2021) - Maffezzoli, Niccolò; Risebrobakken, Bjørg; Miles, Martin W.; Vallelonga, Paul; Berben, Sarah M.P.; Scoto, Federico; Edwards, Ross; Kjær, Helle Astrid; Sadatzki, Henrik; Saiz-Lopez, Alfonso; Turetta, Clara; Barbante, Carlo; et al.
Abstract: Sea ice plays a pivotal role in Earth's climate and its past reconstruction is crucial to investigate the connections and feedbacks with the other components of the climate system. Among the available archives that store information of past sea ice are marine and ice cores. Recent studies on the IP25 biomarker extracted from marine sediments has shown great skill to infer past changes of Arctic sea ice. In ice matrixes, sodium, bromine and iodine have shown potential to store the fingerprint of sea ice presence. The development of an unambiguous sea ice proxy from ice cores, however, has proven to be a challenging task especially in the Arctic realm. In this work we analyze the sodium, bromine and iodine records in the RECAP ice core, coastal eastern Greenland, to investigate the sea ice variability in the northern North Atlantic Ocean through the last 11, 000 years of the current interglacial, i.e. the Holocene. We compare the RECAP records with marine sea ice proxy records available from the northern North Atlantic. We suggest that RECAP sodium concentrations can be associated with variability of sea ice extent, while the bromine-to-sodium ratios and iodine are associated respectively with seasonal sea ice and bioproductivity from open ocean and fresh sea ice surfaces. According to our interpretation, we find that sea ice was at its lowest extent and seasonal in nature during the early Holocene in all regions of the North Atlantic. Increasing sea ice signals are seen from ca. 8–9 ka b2k, in line with long-term Holocene cooling. The increasing sea ice trend appears uninterrupted in the Fram Strait and North Iceland while reaching a maximum ca. 5 ka b2k in the East Greenland region. Sea ice modifications during the last 5000 years display great variability in East Greenland with intermediate conditions between the early and mid Holocene, possibly associated with local fjord dynamics. The last sea ice maximum was reached across all regions 1000 years b2k. Highlights: We review all existing Holocene North Atlantic Ocean sea ice proxy records from marine sediment and ice cores. Sea ice was found at its lowest extent and seasonal in nature during the early Holocene in all regions of the North Atlantic. Increasing sea ice signals are evinced in all regions from ca. 8–9 ka b2k, in line with long-term Holocene cooling. A sea ice maximum is reported ca. 5 ka b2k in East Greenland, followed by great variability in the Late Holocene. The last sea ice maximum was reached across all regions ca. 1000 years b2k.